EXPLORING DIGITAL SELF-EDUCATION: A QUALITATIVE STUDY OF EXPERT INSIGHTS - Denisa Lăcătuș (Styles of Communication)
Generation Z, marked by new media, interconnectedness, and a culture of instant gratification, allocates much of its time to social media platforms. Beyond their multifaceted functions, these platforms have the potential to facilitate learning by enabling teenagers to engage in various stages of knowledge construction, such as sharing ideas, identifying discrepancies, synthesizing information, and applying knowledge. This study investigates the role of Instagram and TikTok as knowledge sources for Generation Z by analyzing both the contributions and concerns related to the consumption of educational content. To achieve this, we conducted expert interviews (N=13) with academicians and practitioners from Romania, Germany, and the USA. The results indicate that social media can facilitate social interactions and identity formation among adolescents while also serving as a source of information and knowledge. However, adolescents should be guided in navigating the potential threats and mitigating their harmful effects. Additionally, the gathered expertise contributed to developing a guideline for practitioners, focusing on the key elements for creating educational content for teenagers.